Construction Labour Measurement in Reinforced Concrete Floating Caissons in Maritime Ports - Pérez-Díaz, Pedro; Martín-Dorta, Norena; Gutiérrez-García, Francisco Javier (Civil Engineering Journal, 2022)
This research work attempts to approach the measuring of the working equipment necessary to make floating caissons for maritime work and their performances. With this objective, an empirical study has been carried out based on the construction of five floating caissons with a rectangular layout of 34.00 meters in length, 17.00 meters in width, and 19.00 meters in depth, lightened with 32 vertical cells. This work was carried out in the port of Granadilla, Tenerife (Spain). The updated scientific literature related to the execution of this type of floating structure refers to the importance of the calculation hypotheses, the actions to be taken into account, the service states or the importance of the choice of materials (concrete and steel). However, scientific research does not seem to face the problem of how to size the working team necessary to execute this type of structure. The work force is approached from the point of view of the adequate sizing of working groups. The important contribution of the article to the project and construction management literature is the development and capability of an easy-to-use optimization model for planning the labour and labour days required in floating caisson construction. The optimization model proposed in this research allows the project managers of a construction company to estimate the labour costs and teams necessary in the execution of the construction. This gives it a competitive advantage both in the construction phase and in the bidding phase for the award of the work. Doi: 10.28991/CEJ-2022-08-02-01 Full Text: PDF